THE SEMIOTIC ANALYSIS OF GALAXY X BTS: THE STRANGE TAYLOR SHOP ADVERTISEMENT - Erna Pranata Putri (Jurnal Sosial Humaniora dan Pendidikan, 2024)
The main purpose of advertising is to market a product or service so that consumers are influenced to buy the product or service. The advertisement itself in its creation requires high creativity so that it looks attractive. In the advertisement, there are verbal and non-verbal messages. The verbal and non-verbal messages contained in this advertisement can be analyzed using semiotic studies. The object of this study is the Samsung Galaxy x BTS: The Strange Tailor Shop advertisement which is aired on Samsung's Youtube channel. This study used the theory of Charles Sanders Pierce by classifying signs into Icons, Indexes, and Symbols which are then analyzed using qualitative methods. The findings of this research indicate that the icons of the Samsung Galaxy x BTS: The Strange Tailor Shop advertisement are Jin and Jungkook, who are globally renowned boyband members and the Samsung Galaxy Note 20 itself, with its premium design. The index refers to the color of the smartphone used in the advertisement, which is Mystic Bronze, creating a premium impression. Meanwhile, the symbol in this advertisement is the Samsung logo, using the distinctive Samsung typeface to convey consistency and a universal visual identity. So, the sign contained in this advertisement shows that the Samsung Galaxy Note 20 is a premium and global smartphone that provides convenience for its users.